Chronic subthreshold subdural cortical stimulation for the treatment of focal epilepsy originating from eloquent cortex. Issue 3 (26th February 2014) - Child, Nicholas D.; Stead, Matt; Wirrell, Elaine C.; Nickels, Katherine C.; Wetjen, Nicholas M.; Lee, Kendall H.; Klassen, Bryan T.
Summary Medically refractory epilepsy remains a major medical problem worldwide. Although some patients are eligible for surgical resection of seizure foci, a proportion of patients are ineligible for a variety of reasons. One such reason is that the foci reside in eloquent cortex of the brain and therefore resection would result in significant morbidity. This retrospective study reports our experience with a novel neurostimulation technique for the treatment of these patients. We identified three patients who were ineligible for surgical resection of the intracranially identified seizure focus because it resided in eloquent cortex, who underwent therapeutic trial of focal cortical stimulation delivered through the subdural monitoring grid. All three patients had a significant reduction in seizures, and two went on to permanent implantation, which resulted in long‐term reduction in seizure frequency. In conclusion, this small case report provides some evidence of proof of concept of the role of targeted continuous neocortical neurostimulation in the treatment of medically refractory focal epilepsy, and provides support for ongoing investigations into this treatment modality. A PowerPoint slide summarizing this article is available for download in the Supporting Information section here.